The Effect of Wooden Number Board on the Ability to Recognize Number Symbols in Children Aged 4-5 Years at TK Negeri Satu Atap Kerinjing - Khotimah, Khusnul; Ilhami, Akmillah (Journal of English Language and Education, 2025)
This study aims to determine the effect of using a wooden number board on the ability to recognize number symbols in children aged 4–5 years at TK Negeri Satu Atap Kerinjing. This research employed a quantitative pre-experimental method with a one-shot case study design. The sample consisted of 10 children from class A, selected using a saturated sampling technique. The results showed that the average posttest score was 75. Data analysis using a one-sample test indicated that the calculated t-value (tₕ) was 4.56, while the table t-value (tₜ) was 1.83. Since tₕ tₜ, it can be concluded that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. Therefore, it can be stated that the wooden number board has an effect on the ability to recognize number symbols in children aged 4–5 years at TK Negeri Satu Atap Kerinjing. This is supported by the fact that 8 out of 10 children were categorized as Developing Very Well (DVW), while the remaining 2 were in the category of Developing As Expected (DAE).